Masculinity of a Major Female Character in Joel Coen’s The Big Lebowski - Maulany Nabilla (Universitas Pendidikan Indonesia (UPI), 2019)
In its early emergence, the theories of masculinity are often associated with men, then female masculinity theories established and shifted the traditional notion of masculinity concept. This paper is intended to scrutinize the portrayal of masculinity in a major female character in a Joel Coen’s 1998 film entitled The Big Lebowski. Female masculinity is chosen as the main topic considering the shift of gender notions in these past few years using the theory proposed by Judith Halberstam (1998). In order to determine whether the characterization of the main object of this paper portrays masculinity, masculinity characteristics theory presented by Levant (1995) and film theory advanced by Amy Villarejo (2007) are also employed in this study. Using the theories mentioned previously, this paper used the dialogues, a number of mise en scene aspects, namely properties, costumes, hair do and makeup, and also cinematography aspects such as camera shots, angles and frames. The data were collected by taking notes on the character;s masculinity traits throughout the film. It is found that the focused character is depicted to have some masculinity traits through her confidence, emotions hiding, the absence of intimacy in sex. Self-reliant, strength, aggression, power, and domination. Thus, this paper proves that masculinity can also be performed with an absence of male body form. Keywords: Female Masculinity, masculinity, masculinity traits, The Big Lebowski